Basic Higher Education: Assessment of the Higher Educational Establishment Pragmatism at the Education Services Market (Economic journal of Lesya Ukrainka Volyn National University, 2017)
Multistage education called forth the «Bachelor» segment at the education services market; it realizes the program of training the seekers of basic higher education. Higher educational establishments have been accumulating educational potential in this segment for a long time. The method for determination of the level of absolute and relative educational pragmatism concerning the bachelor-training educational and professional program in the activity of higher educational establishments in Poltava region has been created; it reveals the level of realization of the establishment educational potential. Absolute educational pragmatism demonstrates the educational establishment level of realization of the licensed amount for bachelor training in a particular specialty. Relative pragmatism demonstrates the establishment level of the use of the licensed amount in relation to other establishments training bachelors in the specialty.
Keywords: higher education, baccalaureate, higher educational establishments, education services market, educational potential, absolute educational pragmatism, relative educational pragmatism, licensed admission, primary demand, secondary demand